Activation of DNA ligase by poly(ADP-ribose) in chromatin. - Ohashi, Y (1983)
To elucidate the molecular mechanism by which poly(ADP-ribose) participates in DNA excision repair, we examined the effect of poly(ADP-ribose) on DNA ligase activity in DNA/histone and reconstituted chromatin systems. The ligase activity was markedly inhibited by histones; the inhibition varied depending on histone subfraction and DNA/histone ratio. Poly(ADP-ribose), either exogenous or synthesized in situ by poly(ADP-ribose) synthetase, reversed this inhibition by histone almost completely. This effect was specific for poly(ADP-ribose); polyanions such as mRNA, rRNAs, tRNA, and synthetic poly(A) were less effective or ineffective. The ligase activity with reconstituted chromatin as the substrate was about half of that with free DNA whereas the activities with these two substrates were almost the same in the presence of poly(ADP-ribose) synthesized in situ. The polymers synthesized under these conditions were exclusively bound to the synthetase. Together with our previous finding that the enzyme is the main acceptor of the polymer in DNA-damaged cells, these results suggest that poly(ADP-ribose) in the synthetase-bound form counteracts inhibition by histones and activates DNA ligase to rejoin DNA strands in polynucleosomal structures.